2019
DOI: 10.1073/pnas.1821409116
|View full text |Cite
|
Sign up to set email alerts
|

α-synuclein−lipoprotein interactions and elevated ApoE level in cerebrospinal fluid from Parkinson's disease patients

Abstract: The progressive accumulation, aggregation, and spread of α-synuclein (αSN) are common hallmarks of Parkinson’s disease (PD) pathology. Moreover, numerous proteins interact with αSN species, influencing its toxicity in the brain. In the present study, we extended analyses of αSN-interacting proteins to cerebrospinal fluid (CSF). Using coimmunoprecipitation, followed by mass spectrometry, we found that αSN colocalize with apolipoproteins on lipoprotein vesicles. We confirmed these interactions using several meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 65 publications
(71 reference statements)
5
35
0
Order By: Relevance
“…5A). This phenomenon was previously observed [27,57,58] and, although not being fully understood, it could be produced by the interaction between α-syn and CSF protein constituents [42,59]. From Fig.…”
Section: Variables Influencing α-Synuclein Seed Amplification Assayssupporting
confidence: 63%
“…5A). This phenomenon was previously observed [27,57,58] and, although not being fully understood, it could be produced by the interaction between α-syn and CSF protein constituents [42,59]. From Fig.…”
Section: Variables Influencing α-Synuclein Seed Amplification Assayssupporting
confidence: 63%
“…The SDS-PAGE was performed as previously described ( 20 ). The sample was mixed in a 3:1 ratio with denaturing loading buffer (106 mM Tris-HCl, 141 mM Tris, 2% lithium dodecyl sulfate (LDS), 10% glycerol, 6% β-mercaptoethanol, 0.51 mM EDTA, 0.22 mM SERVA Blue G-250, 0.175 mM Phenol Red, pH 8.5) and boiled at 95°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, recent studies have suggested that PD may be not only a proteinopathy but also a lipidopathy [22]. Around 40% of CSF alfa-Syn is found in lipoprotein particles [23]. Finally, as in most chronic diseases, inflammation contributes to the pathogenesis of PD.…”
Section: Disease Biology In Pdmentioning
confidence: 99%